Sexual dysfunction in young adult survivors of childhood cancer - A population-based study - Hovén Emma; Fagerkvist Kristina; Jahnukainen Kirsi; Ljungman Lisa; Lähteenmäki Päivi M; Axelsson Ove; Lampic Claudia; Wettergren Lena (United Kingdom, 2022)
Abstract
Objective
To determine the prevalence of sexual dysfunction and to identify the factors associated with sexual dysfunction in young adult childhood cancer survivors.
Methods
All survivors of childhood cancer (aged 19–40 years) in Sweden were invited to this population-based study, and 2546 men and women (59%) participated. Sexual function was examined with the PROMIS Sexual Function and Satisfaction Measure. Logistic regression was used to assess the differences between survivors and a general population sample (n = 819) and to identify the factors associated with sexual dysfunction in survivors.
Results
Sexual dysfunction in at least one domain was reported by 57% of female and 35% of male survivors. Among females, dysfunction was most common for Sexual interest (36%), Orgasm – ability (32%) and Vulvar discomfort – labial (19%). Among males, dysfunction was most common for the domains satisfaction with sex life (20%), Sexual interest (14%) and Erectile function (9%). Compared with the general population, male survivors more frequently reported sexual dysfunction in ≥2 domains (OR = 1.67, 95% CI: 1.03–2.71), with an increased likelihood of dysfunction regarding Orgasm – ability (OR = 1.82; 95% CI: 1.01–3.28) and Erectile function (OR = 2.30; 95% CI: 1.18–4.49). Female survivors reported more dysfunction regarding Orgasm – pleasure (9% versus 5%, OR = 1.86; 95% CI: 1.11–3.13). A more intensive cancer treatment, emotional distress and body image disturbance were associated with sexual dysfunction in survivors.
Conclusions
The findings underscore the need for routine assessment of sexual health in follow-up care of childhood cancer survivors and highlight that those treated with more intensive cancer treatment and who experience concurrent psychological concerns may benefit from targeted screening and interventions.